The Effect of Ethanol Solvent Concentration on Antimicrobial Activities The Extract of Andalas Endophytic Bacteria (Morus Macroura Miq.) Fermentation Product - Larasati Arum Utami; Dwi Hilda Putri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
Anti-Biotic resistance is a health problem globally. It is able to overcome with a new anti-microbial compound that can be produced from Andalas endophytic bacteria. This compound can be obtained through the fermentation process. In order to separate this active-compound, it is needed to use the extraction method. In this method, the solvent is functioned as the extractor. One of the solvent which is commonly used is ethanol. This research is aimed to know the effect of ethanol concentration toward antibacterial activity from extracted bacterial fermentation products of Andalas endophytic bacteria isolate JDT 1B. The fermented products are extracted by using the maceration method. The concentrations are 100%, 80%, 70%. A test of anti-microbial activity is used disk diffusion method. The extracted concentrations tested for each solvent are 50%, 25%, 12,5%, and 6.25%. Anti-bacterial activity is analyzed by using factorial design. The factorial result showed there is no significant contrast between ethanol concentration mentioned toward anti-bacterial activity from extracted bacterial fermentation products of Andalas endophytic bacteria Isolate JDT 1B. The concentration of extracted fermentation product using 70% ethanol has the same inhibition zone as control is 6,25%.